2006
DOI: 10.1002/ddr.20156
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin receptors as drug targets in chronic cardiovascular diseases: the rationale for dual antagonism

Abstract: Endothelin has been described as the most potent vasoconstrictor known. Recent research shows that it is also a growth factor, a promoter of fibrosis and inflammation, and a key initiator of endothelial dysfunction. Endothelin becomes, therefore, a candidate in the pathogenesis of many chronic cardiovascular and fibrotic diseases, and inhibition of endothelin function is a potential therapeutic approach for those diseases. Endothelin receptor antagonists are now established therapy in the treatment of pulmonar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 81 publications
(87 reference statements)
0
19
0
Order By: Relevance
“…In such pathological situations, both ET A and ET B receptors mediate the detrimental actions of ET-1. Because of a "cross talk" between ET A and ET B receptors (Clozel and Flores 2006;Clozel and Gray 1995), selective antagonism of only one receptor subtype may result in compensation by the other receptor subtype and may be insufficient, whereas dual antagonism may be necessary for complete inhibition.…”
Section: Et Receptorsmentioning
confidence: 98%
“…In such pathological situations, both ET A and ET B receptors mediate the detrimental actions of ET-1. Because of a "cross talk" between ET A and ET B receptors (Clozel and Flores 2006;Clozel and Gray 1995), selective antagonism of only one receptor subtype may result in compensation by the other receptor subtype and may be insufficient, whereas dual antagonism may be necessary for complete inhibition.…”
Section: Et Receptorsmentioning
confidence: 98%
“…Despite the numerous reports of ET A -ET B receptor cross-talk in various cell types and tissues, which include a relatively large number of studies in systemic vascular and nonvascular smooth muscle (Clozel and Flores 2006;Watts 2010), it remains unclear whether cross-talk is present in the cerebral vasculature. Using an in situ cranial window preparation, we concluded that ET A -ET B receptor cross-talk was present in the rabbit basilar artery based on the combined observations that the ET-1 contraction was (1) partially relaxed by ET A receptor antagonist and (2) relaxed by ET B receptor antagonist only in the presence of ET A receptor antagonist (Zuccarello et al 1998(Zuccarello et al , 1999.…”
Section: Introductionmentioning
confidence: 97%
“…The rationale for the use of combined ET A and ET B antagonism stems in part from the apparent functional interaction, or "cross-talk," between these receptors (Clozel and Flores 2006;Dhaun et al 2007;Kirkby et al 2008;Trow and Taichman 2009). That is, ET A -ET B receptor cross-talk may limit the efficacy of a selective ET receptor antagonist due to apparent compensation mediated by the other ET receptor subtype (Clozel and Flores 2006).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…ET B receptors act as the major clearance receptor for ET-1 and can participate in the release of nitric oxide. Sometimes alone, but primarily in combination with ET A receptors, ET B receptors can also mediate multiple detrimental effects in disease states, including cellular hypertrophy, inflammation and fibrosis [3]. ET-1 acts in a paracrine and autocrine manner to mediate its broad range of biological activities, which include the control of vasoconstriction and vasodilation via its action on the endothelium and vascular smooth muscle cells, a chemotactic effect on inflammatory cells, such as monocytes and neutrophils, and, as will be discussed further in the present article, a pivotal role in the function and differentiation of fibroblasts and myofibroblasts ( fig.…”
mentioning
confidence: 99%